FACTORS THAT INFLUENCE COUPLES OF FERTILE AGE IN THE USE OF IUD CONTRACEPTION DEVICES IN TITI RANTAI VILLAGE, MEDAN BARU DISTRICT IN 2022 - Natalia, Lidya; Eva Ratna Dewi; Ingka Kristina P; Adelina Sembiring; Fifika Zai; Lamtiar pasaribu (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Background: The National Family Planning (KB) Movement is one of the main activities in an effort to achieve quality families which is directed at controlling the rate of population growth by reducing the birth rate to achieve a balance between population growth and economic growth so as to improve family health Research Objectives: To Analyze Factors Affecting Couples of Reproductive Age in Using IUD Contraceptive Devices in Titi Chain Village, Medan Baru District in 2022. Method: This type of research is an analytical descriptive study with a cross-sectional design and a quantitative approach which is a study that studies the relationship between the independent variable (power) and the dependent variable (effect). The sample is 43 people. Results: The results of the study showed that there was a significant relationship between education, employment, and the number of children with the use of IUD contraception in the Titi Chain Village, Medan Baru District, in 2022, with a p value <0.005. Conclusion: The family planning program guarantees that every person or couple has access to family planning information and services so they can plan the right time for pregnancies, the spacing of pregnancies and the number of children.